Searching for new particles at the Large Hadron Collider: theory and methods for extradimensional supersymmetry - Scoville, J (2015)
The hierarchy problem of the electroweak scale is an intriguing puzzle which can conceivably be solved during upcoming runs of the Large Hadron Collider (LHC). Supersymmetry (SUSY) is an attractive potential solution to this problem, though the fact that no supersymmetric particles have been discovered thus far raises fine tuning of most models to ℴ(1%). Extradimensional SUSY is especially interesting in light of this fact since certain models are easier to reconcile with LHC data. This thesis discusses two different extradimensional SUSY scenarios: auto-concealment and Maximally Natural SUSY (MNSUSY). The auto-concealment mechanism applies when the lightest ordinary superymmetric particle (LOSP), a brane localized state, promptly decays to the Kaluza-Klein (KK) tower of a bulk lightest supersymmetric particle (LSP). This dynamically realizes the compression mechanism for hiding SUSY as decays into the more numerous heavier KK LSP states are favored. LHC limits on LOSP squarks weaken to ≲ 450 GeV while limits on LOSP right-handed sleptons evaporate. Slepton searches perform poorly in this case because LHC analyses are blind to compressed slepton spectra. To help fill this gap, this thesis presents a monojet-like search sensitive to the very compressed range 3 GeV < m ĩ − m∼x01 < 24 GeV. The analysis should allow LHC14 with 100 fb−1 to search for degenerate left-handed selectrons and smuons in the compressed region up to m ĩL ≲ 150 GeV. In addition, it should be sensitive to m ĩL ≲ 110 GeV for auto-concealed SUSY. To expand the class of extradimensional SUSY models the LHC is able to test this thesis also describes the Lagrangian and mass matrices of MNSUSY, which are needed to implement this model in the Feynman rules generator program FeynRules for use in Monte Carlo programs for collider simulations. It also describes benchmark scenarios useful for the first collider phenomenology studies.